Sistem Penjadwalan dan Notifikasi Petugas Ibadah Kelompok Berbasis Web dengan API Pesan Instan - Arifin Paulus Tindi; Oktavianus Lumasuge (Yayasan Literasi Sains Indonesia, 2025)
Managing worship service schedules in churches often encounters various challenges, including delayed dissemination of information, lack of coordination, and frequent miscommunication between administrators and service officers. These issues can lead to confusion, unpreparedness, and reduced effectiveness in church services. To address these problems, this research focuses on designing and developing a web-based worship scheduling system integrated with an automatic notification feature using an Instant Messaging API. The system is developed using the Laravel framework and implemented in the congregation of GMIST Imanuel Petta as a case study. Through this system, administrators can easily create, edit, and distribute worship schedules in real-time. Automatic notifications are sent to each assigned officer according to the schedule, significantly reducing the risk of errors or forgetfulness. The system also includes user access management, history logs, and mobile responsiveness to enhance usability. Testing results show that the system functions effectively, supports better coordination among stakeholders, and improves the efficiency and reliability of worship schedule management. Therefore, this system is expected to be a relevant technological solution to support more modern, structured, and effective church activity management.